Karakterisasi Morfologis dan Fenologi Pembungaan Melati Putih (Jasminum sambac (L.) Aiton) - Fadilah Khoirunnisa; Pinta Murni; M. Erick Sanjaya (Jurnal Penelitian Pendidikan IPA, 2025)
White jasmine (Jasminum sambac (L.) Aiton) is one of the ornamental plants whose flowers are widely used. However, information regarding flower development, especially the flowering phenology of this plant, is still limited. This study aims to obtain information on the flowering phenology of melati putih and the morphological characterization of the flowers. Flowering phenology data was analyzed qualitatively, while flower morphology character data was analyzed quantitatively. The results show that the flowering phenology of melati putih takes place in an average of 26 days with environmental factors being light intensity 337.00-2639.00 lux, air temperature 27-34oC, humidity 61-82%, and rainfall 0.0–9.6 mm. Air temperature and humidity influence the process of bud emergence and the length of time for large buds to develop towards anthesis. The morphological characters of the flower is inflorescentia cymosa, pleiochasial type with trumpet-shaped, white color, and classified as a complete flower. Small flowers have an average flower length of 26 mm and an average diameter of 31 mm. There are 8-10 petals (calyx) with an average length of 8 mm and diameter is 6 mm. The crown (corolla) is composed of 7-10. Each flower has two stamens and a pistil.